Inverse Closed Domination on the Unitary Cayley Graphs - Kiunisala, Edward Manseras; Rosero, Cristopher Salvaor (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
Let Â be a ï¬nite group and e be its identity. Let S be a generating set of G such that and for all . Then the Cayley Graph is deï¬ned by , where Â and Â denoted by . The Unitary Cayley Graph, is deï¬ned by the additive group of the ring Â of integers modulo n and the multiplicative group of Â of its units. If we represent the elements ofby the integers, then it is known that . So has a vertex set Â and the edge set Â In this paper, the domination in graph is extended to a Unitary Cayley graphs, in particular the inverse closed domination on the Unitary Cayley Graphs.